How Does the Quality of Junior High Schools Affect Housing Prices? A Quasi-Natural Experiment Based on the Admission Reform in Chengdu, China - Xiao Tian; Jin Liu; Yong Liu (Land, 2022)
We exploit an admission reform of junior high schools in Chengdu, China, to identify the capitalization effect of high-quality educational facilities on housing prices. Since 2013, some elite junior high schools have conducted an experimental policy called the four-year junior high school project (hereinafter referred to as FJHP). The FJHP reduced the admission chances to elite junior high schools within the FJHP school districts via lottery. Based on 88,745 resale housing transaction records from Chengdu during 2010–2018, we used the difference-in-difference (DID) methodology to estimate the average price effect of the FJHP. Furthermore, we established a DID model with quantile regression to estimate the heterogeneous effect of the FJHP on housing prices. The empirical results show that the implementation of the FJHP reduced the housing prices in the relevant school districts by at least 5.5%, and its price reduction effect increased over time. The quantile regression results show that households with high-priced housing are more sensitive to the change of admission chance to elite junior high schools, which indicates the inequality in accessing high-quality school facilities under the designating admission zone policy. This study concludes with implications for improving the accessibility of school facilities.